Maliseet materials, Floyd G. Lounsbury Papers - Francis, Lorraine; Sherwood, David; Lounsbury, Floyd Glenn; LaPorte, Charlie (1978)
The Maliseet materials in the Lounsbury Papers consists of 4 recordings made on the Tobique Indian Reserve, New Brunswick. The correspondence, in Series I, includes linguisitic work done by Frank Siebert.